U.S. Dental School Applicants and Enrollees, 2015 Entering Class. Issue 12 (1st December 2016) - Wanchek, Tanya; Cook, Bryan J.; Valachovic, Richard W.
Abstract : Every year the American Dental Education Association (ADEA) gathers data on dental school applicants and first‐time, first‐year enrollees. This report analyzes information collected during the 2014–15 application cycle and on first‐time, first‐year enrollees entering dental school in the fall of 2015. The data include applicants' characteristics and academic qualifications and the number and characteristics of the applications received by each dental school. Among the key findings is an upward trend in the number of first‐time, first‐year enrollees, reaching 5, 943 for this class. The number of applicants, 11, 789, was still below the most recent high (13, 742 in 2007), but a slight increase of 44 since 2014 suggests a possible upturn in applicant numbers. Additionally, GPA and Dental Admission Test (DAT) scores remained high, suggesting that dental schools continued to have a strong applicant pool from which to select. The gender distribution for applicants and enrollees was split nearly equally between men and women. Consistent with past years, White students were more than 50% of enrollees. The number of Latino/Hispanic applicants and first‐time, first‐year enrollees continued an upward trend, while the number of other underrepresented groups tended to fluctuate without a clear trend. The data in this report provide a comprehensive view of applicants interested in dental school, allowing schools to compare their applicant pools with the overall applicant pool on a national level. Finally, the information on enrollees offers a first look at the future dental workforce.